The articulation of the university curriculum of the business administration program, from the anthropological theory of the didactic: the case of the subject logic and mathematics I - Jiménez Beleño, Andrés; Jiménez Beleño, Andrés; Administrador, Administrador (Corporación Universitaria Americana, 2022)
Research in mathematics didactics has as a testing ground the work carried out by teachers in the classroom, the transformation of knowledge into skills and abilities, firm and shared, is the result of the techniques they use to mobilize the cognitive resources of students. This didactics-in-use favors the articulation of the mathematics curriculum, which has pertinent relationships with the didactic theories that intervene in the different experiences of significant learning of the study group. The student's study plan is modified to put into play the reconstruction of mathematical knowledge and affect learning.